log(y-x)*1/log(3)=1 3*x+6*y/5=24

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[LaTeX]
log(y - x)    
---------- = 1
  log(3)      
$$\frac{\log{\left (- x + y \right )}}{\log{\left (3 \right )}} = 1$$
      6*y     
3*x + --- = 24
       5      
$$3 x + \frac{6 y}{5} = 24$$
Быстрый ответ
[LaTeX]
$$x_{1} = \frac{34}{7}$$
=
$$\frac{34}{7}$$
=
4.85714285714286

$$y_{1} = \frac{55}{7}$$
=
$$\frac{55}{7}$$
=
7.85714285714286
Численный ответ
[LaTeX]
x1 = 4.857142857142857 + 1.732628516868839e-31*i
y1 = 7.857142857142857 - 4.697885613523936e-31*i
x2 = 4.857142857142857 + 1.732628490121751e-31*i
y2 = 7.857142857142857 - 4.697885546713612e-31*i
x3 = 4.857142857142857
y3 = 7.857142857142857
x4 = 4.857142857150938 - 1.327012720371718e-11*i
y4 = 7.857142857122654 + 3.317531800905905e-11*i
x5 = 4.857142857142857 + 1.732628451665637e-31*i
y5 = 7.857142857142857 - 4.697885528805691e-31*i